(untitled) (Journal of Engineering, 2010)
Base isolation systems have become a significant element of a structural system to enhance reliability during an earthquake. One type of base isolation system is Friction Pendulum Bearing in which the superstructure is isolated from the foundation using specially designed concave surface and bearing to allow sway under its own natural period during the seismic events. This study presents the finite element analysis of Friction Pendulum System (FPS) of a multi-story building and without base isolation, subjected to two real different earthquakes (El Centro & Loma Prieta) by use engineering program (ETABS Nonlinear version 9.5). Comparing with the available experimental data, the application of the current model gives close prediction. It has been shown that as a result of isolation, base shear acting are reduced considerably. A parametric study dealing with the coefficient of friction μ (0.08,0.15 and 0.25) and radius of concave surface R (40 in, 80 in and 400 in) to study the base shear and the displacement of Friction Pendulum System. Overall the base isolated system showed a significant improvement in dynamic response of the model structure by reducing the base shear and increasing the damping of the system